Carbon Nanofiber Reinforced Polymer Composites - Poveda, Ronald L.; Gupta, Nikhil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents an extensive review of literature on the properties of carbon nanofibers (CNF) reinforced polymer composites in conjunction with advances in the production and properties of CNFs. It further provides readers a view into the development of lightweight composites whose properties are tailored and enhanced with micro- and nano-reinforcement, along with results from data comparisons from several published investigations.
Introduction -- Carbon Nanofibers: Structure and Fabrication -- Mechanical Properties of CNF/Polymer Composites.-  Environmental Effects on CNF/Polymer Composites -- Thermal Expansion of CNF/Polymer Composites -- Dynamic Mechanical Analysis of CNF/Polymer Composites -- Electrical Properties of CNF/Polymer Composites -- CNF-Reinforced Multiscale Composites.
Keywords: Materials -- Analysis; Polymers; Characterization and Analytical Technique; Polymers